Skin metastasis within radiation field in treated squamous cell carcinoma of larynx - Selvaraj, Vinodh Kumar; Gudipudi, Deleep Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Cutaneous metastasis from squamous cell carcinoma (SCC) of larynx is very uncommon. Skin mestatsis in a treated of case of SCC larynx is considered to be a sign of impending distant metastasis and dismal prognosis. There are very few case reports in literature describing such presentations, and very minimal information on treatment options available for these patients. Here, we describe two cases of locally advanced SCC larynx treated with chemoradiation upfront, who later presented with cutaneous metastasis in neck within the previous radiation field. Evaluation for distant metastasis was done and started on palliative chemotherapy. The first patient had complete resolution of cutaneous nodules post 8 cycles of weekly palliative chemotherapy. However, post 18 cycles of chemotherapy, he developed a metachronous primary in upper thoracic oesophagus and disease progressed loco-regionally too. The second patient’s general condition deteriorated after 1st cycle of palliative chemotherapy, hence was offered best supportive care. Cutaneous nodules in a treated SCC of larynx must raise the suspicion of metastasis, warranting histological examination, and whole-body imaging work-up to rule out distant metastasis. Palliative chemotherapy must be advocated in all eligible patients to delay disease progression. Best supportive care can be offered in patients not eligible for chemotherapy.